A Comparative Analysis Between The Hairy Ape and Emperor Jones by Eugene O'Neill from Expressionism Viewpoint - Nezhad, Zahra Yousefi; Ahmadian, Moussa (Mediterranean Journal of Social Sciences, 2012)
Expressionism in literature was a revolutionary movement against realism and naturalism. As a twentieth centurymovement, it is the subject of the inner world. Like most artistic movements, it is applied to lots of art forms including Paintings,Architecture, Cinema, and Music. Dramatists like Elmer Rice and Eugene O'Neill introduced Expressionism to AmericanLiterature. This paper is a comparative study of O'Neill's The Hairy Ape and Emperor Jones based on expressionism viewpoint.Its aim is to find the expressionistic features and to compare the similarities and differences between these two works. Thefeatures and principles of expressionism in drama include: structure (for example, one-act play), main focus on protagonist andhis inner conflicts, tragic ending, unnamed minor characters, employing music and light (as two prominent features ofexpressionism), applying symbols and colors, monologue and soliloquy or telegraphic dialogue, etc. In this paper, these werefeatures of analysis. The research revealed the fact that there are similarities and differences between the two pieces of dramain question. Although the two plays, Emperor Jones and The Hairy Ape written by one author (Eugene O'Neill) and in one periodof his life (1920-1921), and both are known as expressionist works, still there are some differences in applying expressionisticfeatures. The similarities and differences are discussed followed by some suggestion for further research.